Performance evaluation of continuous and discontinuous pulse width modulation techniques for grid‐connected PWM converter - Fahem, Kawther; Chariag, Dhia Elhak; Sbita, Lassaad (International transactions on electrical energy systems, 2018)
Summary Power quality has become an important issue as the number of nonlinear loads and power electronic equipment connected to the grid is continuously growing. Grid‐connected PWM converters have been largely exploited in many industrial applications; they still present an interesting research subject in terms of improving current waveform quality and providing an accurate DC‐link voltage. Besides the different control strategies proposed in the literature corresponded to a specific requirement performance, the modulation techniques also present a critical aspect in the design of the control system. In this paper, several modulation techniques including continuous and discontinuous modulations have been studied and analyzed for the control of grid‐connected PWM converter. An extensive simulation and experimental tests have been carried out in order to investigate the influence of the studied modulation techniques on the harmonic current distortion delivered by the converter under different unbalanced grid conditions.